Effects of blended teaching model based on curriculum ideology and politics on humanistic care and communication skills of nursing interns (基于课程思政的混合式教学对实习护生人文关怀及护患沟通能力的影响) - WANG Yuena (王岳娜); GAO Yan (高燕); XU Yuanle (许远乐); LEI Shaohua (雷少华); WANG Hong (王红); LI Xiaoqiang (李小强); XI Yun (席云) (中西医结合护理)
Objective To investigate the effect of blended teaching model based on curriculum ideology and politics on humanistic care and communication skills of nursing interns. Methods A total of 96 nursing students were divided into the control group and observation group accoding to the sequence of clinical internship time, with 48 cases in each group. Conventional teaching method was adopted in the control group, while a blended teaching model based on curriculum ideology and politics was used in the observation group. Teachers had recorded training videos about humanistic care in basic nusing procedures and conducted pre-class online preview. Students were taught by using on-site demonstration, practical operation and interactive teaching during internship, and their knowledge and skills were enhanced through after-class online tutoring. A blended teaching model was adopted to ensure the knowledge internalization and mastery. The outcomes of operation exam and assessment on humanistic care items, Caring Ability Inventory (CAI) and nurse-patient communication skills scale were compared between two groups. Results Nursing students in the observation group achieved higher scores of operation exam and assessment on humanistic care items than those in the control group(P＜0. 01). The total score and subscales score of CAI in the observation group than those in the in the control group(P＜0. 01). The total score and subscales score of nurse-patient communication skills scale in the observation group than those in the in the control group(P＜0. 05). Conclusion The blended teaching model based on curriculum ideology and politics can improve the humanistic care and communication skills of nursing interns. (目的 探索混合式教学融入课程思政对实习护生人文关怀能力、护患沟通能力的影响。方法 选取医院实习的96名护生作为教学活动的研究对象, 按照实习学年分成对照组与观察组, 每组48人。对照组采用常规教学模式; 观察组采用基于课程思政的混合教学模式, 教师在基础护理操作教学设计中融入课程思政, 录制全程人文关怀的基础护理操作教学视频, 实施课前线上预习, 课中现场示范与实操及互动教学, 课后线上成果固化; 护生采用混合式学习方式, 加深知识内化与掌握。课程结束后, 分析比较两组护生操作考核成绩及操作考核中人文关怀条目成绩、人文关怀能力、护患沟通能力。结果 观察组护生操作考核成绩及操作考核中人文关怀相关条目成绩均高于对照组, 差异有统计学意义(P＜0. 01)。观察组人文关怀能力评价量表(CAI)总分和耐心、理解、勇气维度评分均高于对照组, 差异有统计学意义(P＜0. 01)。观察组护生临床沟通能力量表总分和各个维度评分高于对照组, 差异有统计学意义(P＜0. 05)。结论 在临床基础护理教学中, 运用基于课程思政的混合式教学模式, 能有效提高护生人文关怀能力和护患沟通能力。)